Digitalisasi Potensi Wisata Riau dan Kepulauan Riau Berdasarkan Puisi-Puisi dalam Portal Web Riausastra.Com - Piliang, Wilda Srihastuty Handayani (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
This study aims to identify and map tourism potentials in Riau and the Riau Islands through the analysis of poems on the Riausastra.com web portal, integrating them with Geographic Information Systems (GIS) for digital-based tourism promotion. The research employs a Research and Development (R&D) method, including poem collection, content analysis, GIS mapping, and strategy formulation. The results reveal that the poems depict diverse tourism destinations, such as nature, culture, history, and culinary, which are then interactively mapped via GIS. The key innovation lies in the development of the Cakap Bumi Melayu portal, combining literature, technology, and tourism to enhance accessibility and appeal. This study significantly contributes to local wisdom-based tourism development and strengthens the integration of literature and digital technology.